2023
DOI: 10.3389/fcvm.2022.969148
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of hypertension and correlation with mental health in women with burning mouth syndrome: A case-control study

Abstract: BackgroundThe relationship between hypertension (HTN) and chronic pain is still a matter of debate, and its prevalence in patients with burning mouth syndrome (BMS) has never been evaluated. This study aimed to assess the prevalence of HTN in women with BMS and to evaluate its relationship with potential predictors such as risk factors for cardiovascular diseases, pain, and mental health status analyzing differences with healthy women.MethodsIn total, 250 women with BMS (WBMS) were prospectively recruited and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 85 publications
2
5
0
Order By: Relevance
“…In our study, the presence of HT in the BMS group was 84.8%, which is consistently higher than the frequency identified in studies conducted in other countries. For example, Adamo and collaborators reported a HT frequency of 55% in BMS Italian patients [17], with a lower frequency of 51.2% considering only the female patients [18]. In line with our results, these authors also found a significantly higher frequency of HT in BMS patients compared to controls [17,18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, the presence of HT in the BMS group was 84.8%, which is consistently higher than the frequency identified in studies conducted in other countries. For example, Adamo and collaborators reported a HT frequency of 55% in BMS Italian patients [17], with a lower frequency of 51.2% considering only the female patients [18]. In line with our results, these authors also found a significantly higher frequency of HT in BMS patients compared to controls [17,18].…”
Section: Discussionsupporting
confidence: 91%
“…A larger study conducted in Italy, involving over 200 patients and 200 controls, has found a statistically significant higher proportion of BMS patients suffering from hypertension compared to controls [17]. The same group of authors analyzing a cohort of BMS women compared to not-affected women found that, in addition to hypertension, hypercholesterolemia was more frequent in the BMS women [18]. Another report on the Japanese population, investigating the prevalence of 13 diseases in BMS patients, found that most of the investigated diseases seemed to have little influence on the majority of patients with BMS [19].…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…The data on depression are in line with those reported in the literature. Indeed, many research groups reported higher levels of depression in BMS patients compared to controls measured by HADS ( Malik et al, 2012 ; Lopez-Jornet et al, 2015 ; Leuci et al, 2022 ) and other instruments, including HAM-D ( Nasreddine et al, 2005 ; Canfora et al, 2021 , 2023 ) and the Beck Depression and Anxiety Inventory (BDI) ( Buljan et al, 2008 ; Malta et al, 2021 ). In addition, in agreement with literature data ( Chainani-Wu et al, 2011 ; Adamo et al, 2013 ; Lopez-Jornet et al, 2015 ; Adamo et al, 2018 ; Rezazadeh et al, 2021 ), our outcomes confirmed a higher frequency of poor sleep quality in BMS patients than controls.…”
Section: Discussionmentioning
confidence: 99%
“…A particular condition that requires special attention from physicians is preeclampsia, the leading cause of maternal and neonatal death, for which an early diagnosis and a timely initiated and well-conducted antihypertensive therapy are essential (25-27). With the sole exception of pregnancy, the current good clinical practice guidelines do not make any differences between men and women regarding the general therapeutic approach (28), even if a gender-related response to therapy has been suggested (29)(30)(31).…”
Section: Contributions To the Topicmentioning
confidence: 99%